A Photovoltaic Self‐Powered Gas Sensor Based on All‐Dry Transferred MoS2/GaSe Heterojunction for ppb‐Level NO2 Sensing at Room Temperature. Issue 14 (24th May 2021) - Niu, Yue; Zeng, Junwei; Liu, Xiangcheng; Li, Jialong; Wang, Quan; Li, Hao; Rooij, Nicolaas Frans de; Wang, Yao; Zhou, Guofu
Abstract: Traditional gas sensors are facing the challenge of low power consumption for future application in smart phones and wireless sensor platforms. To solve this problem, self‐powered gas sensors are rapidly developed in recent years. However, all reported self‐powered gas sensors are suffering from high limit of detection (LOD) toward NO2 gas. In this work, a photovoltaic self‐powered NO2 gas sensor based on n‐MoS2 /p‐GaSe heterojunction is successfully prepared by mechanical exfoliation and all‐dry transfer method. Under 405 nm visible light illumination, the fabricated photovoltaic self‐powered gas sensors show a significant response toward ppb‐level NO2 with short response and recovery time and high selectivity at room temperature (25 °C). It is worth mentioning that the LOD toward NO2 of this device is 20 ppb, which is the lowest of the reported self‐powered room‐temperature gas sensors so far. The discussed devices can be used as building blocks to fabricate more functional Internet of things devices. Abstract : A photovoltaic self‐powered gas sensor based on MoS2 /GaSe heterojunction is fabricated via mechanical exfoliation and all‐dry transfer method. Under visible light illumination, large numbers of free carriers (electrons and holes) are produced and separated in the heterojunction, thus the MoS2 /GaSe heterojunction can achieve self‐powered gas sensing toward ppb‐level NO2 at room temperature.